2016
DOI: 10.1371/journal.pone.0148481
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental Eye Movement (DEM) Test Norms for Mandarin Chinese-Speaking Chinese Children

Abstract: The Developmental Eye Movement (DEM) test is commonly used as a clinical visual-verbal ocular motor assessment tool to screen and diagnose reading problems at the onset. No established norm exists for using the DEM test with Mandarin Chinese-speaking Chinese children. This study aims to establish the normative values of the DEM test for the Mandarin Chinese-speaking population in China; it also aims to compare the values with three other published norms for English-, Spanish-, and Cantonese-speaking Chinese ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…The DEM ratio, which has been purported to provide a measure of reading‐related saccadic eye movement performance independent of RAN, was not significantly associated with any of the NAPLAN academic measures in the current study. This lack of association could not be explained by a lack of variation in performance in the group, which ranged from 0.85 to 1.91, suggesting that a number of children within the sample had oculomotor dysfunction when compared to samples of similar age . While other studies have reported significant relationships between the DEM ratio and reading outcomes, they also noted that the associations were stronger for the horizontal and vertical times.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The DEM ratio, which has been purported to provide a measure of reading‐related saccadic eye movement performance independent of RAN, was not significantly associated with any of the NAPLAN academic measures in the current study. This lack of association could not be explained by a lack of variation in performance in the group, which ranged from 0.85 to 1.91, suggesting that a number of children within the sample had oculomotor dysfunction when compared to samples of similar age . While other studies have reported significant relationships between the DEM ratio and reading outcomes, they also noted that the associations were stronger for the horizontal and vertical times.…”
Section: Discussionmentioning
confidence: 63%
“…This lack of association could not be explained by a lack of variation in performance in the group, which ranged from 0.85 to 1.91, suggesting that a number of children within the sample had oculomotor dysfunction when compared to samples of similar age. 43 While other studies have reported significant relationships between the DEM ratio and reading outcomes, 36,39 they also noted that the associations were stronger for the horizontal and vertical times. Furthermore, the horizontal and vertical DEM times have shown better repeatability than the ratio, 44 which may explain their stronger associations with academic outcomes in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Since the DEM test is a language-specific test and there is a different learning curve for each country which depends on socio-demographic, political, and cultural differences, the normative data in the first years of school become important. Normative values are actually available for nine languages and countries: English, 5 two for Spanish, 14 , 57 Cantonese, 15 Japanese, 56 Portuguese, 58 Italian, 30 Mandarin, 59 Latvian, 16 and French 60 languages.…”
Section: Normsmentioning
confidence: 99%
“…Some comparisons that have been made with seven of them showed that some are different, particularly for the younger group and in the lower percentile rank. 15 , 30 , 58 , 59 Coherently, each specific norm has to be used for each language. Conversely, other direct comparisons did not find differences.…”
Section: Normsmentioning
confidence: 99%
“…The authors in [8,14] explained the differences between the DEM test and the adult DEM test. Furthermore, the DEM test can be used to determine the normative values of the DEM test for children speaking different languages [15], and can show the effects of amblyopia in children [16]. It can also be used to determine whether colored overlays could enhance reading performance or scanning ability [17].…”
Section: Background Theorymentioning
confidence: 99%